The ballad of Tom Dooley : a ballad novel - McCrumb, Sharyn, 1948- (Thomas Dunne Books, 2011)
A story inspired by a true crime made famous by the Kingston Trio's folk song recording reimagines the events surrounding the murder of North Carolina mountain girl Laura Foster and the hanging of her lover, Tom Dula, in a meticulously researched account that reveals additional information that may prove Dula's innocence.